An analysis of influence factors of sports bra comfort evaluation based on different sizes. Issue 12 (2nd December 2019) - Liu, Kaixuan; Zhang, Lingxi; Zhu, Chun; Zhao, Xueqing; Lu, Wenqin; Li, Michael; Wang, Jianping
Abstract: The purpose of this article was to find the main influence factors of sports bra comfort evaluation of different sizes women (small/medium size; large size) of different styles commercial sports bra. Thirty-one women in different bra sizes were chosen to evaluate 11 different styles sports bras. According to different sizes, the main influence factors were extracted by factor analysis and all the product samples were classified by Q-cluster analysis. And the comfort evaluation results of different two sizes were compared to find the differences. The results find that breast stability, wearing comfort and breast shape are the three key factors for sports bra comfort evaluation. By comparison of comfort evaluation results of different two sizes, the conclusions show that the large size is more concern about shoulder strap pressure, breasts gather effect, cup inclusiveness and lower breast stability, while the small and medium size pays more attention to the possibility of wearability factor. A classification-positioning model of sports bra products was established. The results can provide theoretical basis and guidance for the research and comfort evaluation of sports bras for underwear enterprises, and also provide reference value for women customers.